MELAMPAUI POSTMODERNISME: KAJIAN TEORITIS TERHADAP PEMIKIRAN ROBERT SAMUELS TENTANG AUTOMODERNITY - Wirawan, I Made Aryasuta (Sosioglobal, 2016)
The rapid development of information technology and its futuristic lead us into a new era that changed the face of human civilization. New media has become a base structure in accelerating the development of the global community in the last two decades. Digital and virtual sides attached to the new media has brought human interaction and community level to the most complex. Social interaction is in the form of the peak of its evolution where the boundaries between the real and the virtual becomes blurred, and as if no longer relevant when distinguishing the two realms. Human habitus which was originally driven by empirical external world is now automatically changed since information technology products such as mobile phones are no longer exist merely as a communication tool but also as a means of kontrolling and diggers knowledge. This article is a kind of theoretical review of Robert Samuels theory named automodernity as a new cultural stage. He explains emancipatory ideals that originally carried the new media makes us are in a paradoxical situation for the automation of social and individual autonomy attract each effect, Automodernity is a reaction to postmodern emphasis on social and cultural conflict with individual autonomy celebrate the ability to exploit and explore irregularities (unregulated) and the social systems automatically.Keywords: postmodernity, automodernity, autonomy, automated technology, digital youth